Retrospection and re-orientation in Dante's Ante-Purgatory - Dormor, C (2022)
This thesis investigates Dante’s use of retrospection in Ante-Purgatory or, more specifically, of intratextual eches of Inferno in Purgatorio I-IX. Building upon earlier work on intratextuality in the poem, the thesis highlights and discusses vertical echoes between cantos of the same number, diegetic, and episode-related parallels, as well as other forms of repetition, including recalls of specific lexical fields, syntagms, and rhyme patterns. In so doing, the thesis aims, firsltly, to demonstrate that Ante-Purgatory constitutes a privileged space for retrospective reading, and secondly, to broaden the manner in which we conceive of intratextuality within the Commedia. This is achieved through considering the ways in which Dante develops a programme of recalls across the Ante-Purgatory cantos to the beginning of Inferno, to Limbo, and to the encounter with Ulysses, and by considering several less-established modes of retrospection, including thematic parallels, similarities in the presentation of certain figures, and landscape echoes. In Chapter 1, I consider how retrospection in Purgatorio I and II contributes to the re-orientation of the reader at the beginning of the new cantica. In Chapter 2, I explore the thorny and problematic issue of Virgil’s damnation which, I argue, is developed especially in cantos III-VI through recalls to Inferno IV. In Chapter 3, I explore the value of landscape reading and how the poet makes important recalls to infernal landscapes and modes of travel through Hell. Overall, we see that in the liminal and transitional zone that is Ante-Purgatory, the preoccupation with retrospection interrogates and problematizes the division between the damned and the saved in the passage from Hell to Purgatory. Though retrospective elements are of course present throughout the Commedia, I argue that Ante-Purgatory is a particularly privileged space for retrospection precisely because of its liminal textual and geographic position.